Method for calculating the surface tension of hydrocarbons - E. V. Rytova; B. A. Arutyunov (Тонкие химические технологии, 2013)
A method of surface tension calculation used by Sugden is based on the difference in the densities of a liquid and its vapor. A similar result was obtained by Bachynskyi. To expand the field of application of the formula for polar liquids Steele polarity factor was introduced. The experimental data have an error of up to 3%. The generalized processing of the experimental data by the surface tension of hydrocarbons enables to obtain a calculation formula for determining the temperature dependence of the modified surface tension of hydrocarbons. Parameters (temperature and surface tension) corresponding to minimum of free energy for the liquid – vapor phase transition were used as modification scales when constructing the generalized dependencies. The developed method was used to summarize the experimental data by the surface tension of gas condensates of different areas.